Cardiovascular Risk Factors and Chronic Kidney Disease—FGF23: A Key Molecule in the Cardiovascular Disease. (12th January 2014) - Jimbo, Rika; Shimosawa, Tatsuo
Abstract : Patients with chronic kidney disease (CKD) are at increased risk of mortality, mainly from cardiovascular disease. Moreover, abnormal mineral and bone metabolism, the so-called CKD-mineral and bone disorder (MBD), occurs from early stages of CKD. This CKD-MBD presents a strong cardiovascular risk for CKD patients. Discovery of fibroblast growth factor 23 (FGF23) has altered our understanding of CKD-MBD and has revealed more complex cross-talk and endocrine feedback loops between the kidney, parathyroid gland, intestines, and bone. During the past decade, reports of clinical studies have described the association between FGF23 and cardiovascular risks, left ventricular hypertrophy, and vascular calcification. Recent translational reports have described the existence of FGF23-Klotho axis in the vasculature and the causative effect of FGF23 on cardiovascular disease. These findings suggest FGF23 as a promising target for novel therapeutic approaches to improve clinical outcomes of CKD patients.